Coherence Problems of EFL Students’ Writing in Light of the Gricean Maxims - Khonamri, Fatemeh; Hashemi, Ehsan; Pavlikova, Martina; Petrasova, Bozena (Journal of Education Culture and Society, 2021)
Aim. In academic writing, lack of coherence is thought to occur mostly due to the lack of necessary linguistic skills and knowledge in L2. Thus, the analysis of a written text is concerned with understanding the local relations among the ideas conveyed in a text.Concept. As is usually the case, students writing in a second language generally produce texts that contain varying degrees of grammatical and rhetorical errors. Most of the studies have been conducted with only one criterion for the analysis of coherence and they reported different results. Also, most of them have been conducted on a small scale in terms of the number of participants, and writing samples collected. Therefore, this study tries to investigate the coherence problems/errors of university students in their writing, if any, on a fairly large scale in light of the Cooperative principle and its maxims.Results and conclusion. The study revealed that the basic problem of the students in their essay writing was the way the text should be structured with reference to how cohesion and coherence are established. In the analysis of maxim violations, the violation of the Quality maxim was identified as making overgeneralisations or giving inadequate or no evidence/support for the claims/ideas. The violation of the Quality maxim indicates that students tend to do it due to their linguistic inadequacies.